BS EN 16307-1. Industrial trucks. Safety requirements and verification. Part 1. Supplementary requirements for self-propelled industrial trucks, other than driverless trucks, variable-reach trucks and burden-carrier trucks (11th December 2018) - British Standards Institution,
No abstract available